Hubungan Tambahan Penghasilan Pegawai (TPP) Dan Kemampuan Kerja Dengan Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Penataan Ruang Provinsi Bengkulu - Gustini Gustini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the relationship of employee’s additionalincome (TPP) with their performance and to investigate the relationship between employee’s ability and performance in the Public Works and Spatial Planning Office of Bengkulu Province. The analytical method used in this study is Spearman rank correlation and hypothesis testing.Based on the calculation of the Spearman rank correlation coefficient, it is known that the rank spearman correlation analysis of the relationship between TPP and the performance of employees in the Public Works and Spatial Planning Office of Bengkulu Provinceobtained 0.74 strong criteria because the correlation results were in the coefficient interval between 0.600 - 0.799. From the results of the hypothesis test the relationship between the TPP and the performance of employees in the Public Works and Spatial Planning Office of Bengkulu Provinceis 7.124 so it can be concluded that TPP has a significant relationship with the performance of employees in the Public Works and Spatial Planning Office of Bengkulu Provincebecause the value of t is greater than t table (1.681). Rank spearman correlation analysis of the relationship of work ability with the performance of employees in the Public Works and Spatial Planning Office of Bengkulu Province obtained a value of 0.84 very strong criteria because the correlation results lie in the coefficient interval between 0.800 - 1,000. From the results of hypothesis testing the relationship between work ability and the performance of employees in the Public Works and Spatial Planning Office of Bengkulu Provinceis 10.038 so it can be concluded that work ability (X2) has a significant relationship with the performance of employees in the Public Works and Spatial Planning Office of Bengkulu Province because the value of t is greater than t table (1,681).